ANALISIS KEPUASAN KONSUMEN DENGAN MENGGUNAKAN METODE CUSTOMER SATISFACTION INDEX (Studi Kasus : C’Bezt Taman Griya) - Simanjuntak, Pinondang; Satriawan, I Ketut; Mulyani, Sri (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 7 No 2 (2019): JuniDO - 10.24843/JRMA.2019.v07.i02.p02, 2019)
The purpose of this study was to know the attributes that are considered important by consumers and to know the level of customer satisfaction at C'Bezt Taman Griya. The method used is Slovin Method for determining samples and customer satisfaction index (CSI) method for data processing. Tests for reliability and validity were carried out at Jaya Fried Chicken Siligita and research site in C’Bezt Taman Griya. The number of samples used was 97 respondents. The attributes that are considered important by consumers based on the level of importance are the taste of food, the behavior of employees in serving consumers, and cleanliness of the location. Based on the level of satisfaction is the speed in serving consumers, taste of food, seriousness in serving consumers. The level of customer satisfaction C'Bezt Taman Griya is 74.63% with the level of Customer Satisfaction criteria that is satisfied. Keywords : Consumer Satisfaction, Consumen Satisfaction Index, C’Bezt.